The Interaction Of Feldspar, Mica And Quartz With Different Collectors During Froth Flotation - Ibrahim, Ismail (2012)

(untitled)
Malaysian pegmatite sample containing feldspar, quartz and mica as major minerals were studied. XRF, XRD, ore microscope, FESEM equiped with EDX and AAS were extensively used in the characterization studies. The amount of feldspar in the sample was determined follow the feldspar convention and found that at approximately 61% feldspar (majority is microcline), 27% quartz and 4% mica. FESEM observation found that quartz was interlocked with feldspar in the size range between 10 to 1400 μm required proper liberation before proceed to concentration (flotation. Iron bearing presented as free discrete particle and interlock with quartz and feldspar was removed by magnetic separator. For liberation purpose, the sample was ground for 17 minutes and sieved. therefore 80% of the sample was accumulated in the fraction -600 μm with approximately 90% liberated. The adsorption behavior of N-tallow 1,3–propanediamine-dioleate (duomeen TDO) on feldspar and quartz or coco amine on mica, feldspar and quartz was assessed through zeta potential, contact angle, fourier transformed infra-red (FTIR) and Hallimond tube. Zeta-potential results showed that the isoelectric points of the feldspar, quartz and muscovite were 1.80, 1.9 and 2.0 respectively. By gradually adding duomeen TDO and coco amine, the contact angle of feldspar and quartz (with duomeen TDO) and mica, feldspar and quartz (with coco amine) increased leading to enhance hydrophobicity, but with a decrease in its free energy and components. Monolayer of duomeen TDO was developed on the feldspar particle when 1.2 ppm of the collector used at pH 2. This was indicated by the contact angle of water Өwater = 90o. FTIR was used to examine duomeen xxvi TDO adsorbed on feldspar and quartz whereas coco amine on surfaces of feldspar, quartz and mica between the region 3000-2800 cm-1 at various dosage and pH. Hallimond tube flotation test results at different dosage of duomeen TDO (for feldspar) and coco amine (for mica) show the lowest amount of quartz floated at pH 2, and recoveries for both feldspar and mica increased corresponding with collector dosages. The optimum dosage of duomeen TDO and coco amine correlated with highest feldspar and mica recoveries were 40 ppm and 60 ppm respectively. Diesel promote the flotation selectivity of mica achieved the optimum at 30 ppm. Bench scale feldspar flotation using sulfuric acid (H2SO4) as a modifier and a mixed type of collector duomeen TDO were studied. Besides, the flotation of muscovite using coco amine collector was also investigated, and found that 79.09% of feldspar was discovered with a grade of 86.18%. The parameters were particle (-300+45) μm, pH 2 (H2SO4 modifier), percent of solids (20%), Aero 65 (90 g/t), duomeen TDO (600 g/t) and Aero 65 (90 g/t). While for mica flotation, 90% of mica was discovered with a grade of 75.38% at pH 2, percent of solids (20%), coco amine (170 g/t), pine oil (150 g/t), diesel (150 g/t) and particle size (-600+45) μm.